Blockchain in Digital Transformation: Enhancing Security, Transparency, and Efficiency in Modern Systems - Handra, Tessa; Purnama, Suryani; Jati Kusumo, Ariya; Bennet, Daniel (Blockchain Frontier Technology, 2024)
Blockchain technology has emerged as a transformative force in the digital transformation of industries, particularly in enhancing security, transparency, and operational efficiency. This paper aims to explore the practical applications of blockchain in various sectors, including supply chain management, healthcare, and finance, and assess its ability to address challenges like decentralization, cryptographic security, and consensus mechanisms. Through a comprehensive literature review and case study analysis, this study examines how blockchain technology fosters trust, reduces fraud, and improves the efficiency of digital systems by providing tamper-proof records and automating processes through smart contracts. The research also identifies significant barriers to blockchain adoption, such as scalability issues, regulatory constraints, and interoperability problems that hinder its widespread implementation. By evaluating these obstacles, the paper offers insights into the technological and policy challenges that need to be overcome to facilitate blockchain's broader use. This study contributes to the growing body of knowledge by showcasing the potential of blockchain to revolutionize industries beyond its initial use in cryptocurrencies. The novelty of this research lies in its focus on blockchain's applications in real-world business systems, emphasizing its role in digital transformation strategies. The paper concludes by recommending further research and technological innovations to address the scalability and regulatory gaps, as well as strategies for accelerating blockchain adoption. Ultimately, blockchain's ability to enhance the security, transparency, and efficiency of modern systems positions it as a key driver of future digital transformations.